Identification of The Antioxidant Activity of Bamboo Shoots a Raw Material for Manufacturing Lemea - Yenni Okfrianti; Catur Herison; Fahrurrozi Fahrurrozi; Budianto Budianto (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This research aims to determine the antioxidant activity of bamboo shoots used as raw material for making lemea, a local fermented food. Methodology: The antioxidant activity of bamboo shoots was tested using the DPPH method. The research involved creating ethanol extracts from bamboo shoots of Mayan bamboo (Gigantochloa robusta), Betung bamboo (Dendrocalamus asper), and yellow bamboo (Bambusa vulgaris). The extracts were analyzed using a spectrophotometer at a wavelength of 517 nm after 30 minutes of incubation. Results: The study found that bamboo shoots used as raw material for lemea exhibited weak to very weak antioxidant activity. The IC50 values were 387.608 ppm for yellow bamboo shoots, 666.907 ppm for Betung bamboo shoots, and 799.593 ppm for Mayan bamboo shoots. Findings: The antioxidant activity of the bamboo shoots varied, with yellow bamboo shoots showing the highest antioxidant activity among the three types tested. Novelty: This research provides new insights into the antioxidant properties of bamboo shoots, specifically those used in making lemea. Originality: The study offers a detailed analysis of the antioxidant activity of different bamboo shoots, contributing to the understanding of their potential health benefits. Conclusions: Bamboo shoots, the raw material for making lemea, have weak antioxidant activity, with yellow bamboo shoots exhibiting the highest activity. Type of Paper: Experimental Research Article